2019
DOI: 10.7717/peerj.6683
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR4435-2HG predicts poor prognosis in patients with colorectal cancer

Abstract: Background LncRNA MIR4435-2HG is observed in a variety of cancers, while its role in colorectal cancer is unknown. We aimed to demonstrate the relationship between MIR4435-2HG and colorectal cancer based on The Cancer Genome Atlas (TCGA) database. Materials and Methods Patients with colorectal cancer were collected from TCGA. We compared the expression of MIR4435-2HG in colorectal cancer and normal tissues with Wilcoxon rank sum test, and logistic regression was used to evaluate the relationship between MIR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 22 publications
5
43
0
Order By: Relevance
“…11 Additionally, the emerging evidences have displayed that lncRNA MIR4435-2HG is correlated with the occurrence and progression of many cancers. [12][13][14][15] A previous study has showed that overexpression of lncRNA MIR4435-2HG increases the cell viability and migration in colon adenocarcinoma (COAD) cells, which eventually promotes the development of colorectal cancer (CRC) in mice. 14 Another study has disclosed that MIR4435-2HG expression is markedly increased in hepatocellular carcinoma (HCC) and promotes the proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, the emerging evidences have displayed that lncRNA MIR4435-2HG is correlated with the occurrence and progression of many cancers. [12][13][14][15] A previous study has showed that overexpression of lncRNA MIR4435-2HG increases the cell viability and migration in colon adenocarcinoma (COAD) cells, which eventually promotes the development of colorectal cancer (CRC) in mice. 14 Another study has disclosed that MIR4435-2HG expression is markedly increased in hepatocellular carcinoma (HCC) and promotes the proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…We found that LINC00978 knockdown inhibited the phosphorylation of several signaling molecules in the MAPK/ERK pathway. Similarly, in colorectal cancer, Ouyang et al [42] demonstrated that LINC00978 was involved in the P38/MAPK pathway by performing functional annotation based on Gene set enrichment analysis, and they suggested that LINC00978 might promote colorectal cancer cell growth, metastasis, and poor survival via P38/MAPK pathway. ERK, p38, and JNK have been shown to have profound effects on HCC cell differentiation, proliferation, survival, and invasion [40,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Profiting from the development of RNA sequencing and bioinformatics analysis, investigation of the heterogenetic pathology of AML has become more profound, among which the role of ncRNAs in development and progression of AML has been increasingly revealed in recent decades, including forming regulatory networks that could mediate multiple pathways related to AML . Nonetheless, previous studies investigating the roles of lncRNAs in AML only begin recently, and are quite limited, even though lncRNAs have been found to be crucial genetic factors in other malignancies …”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Nonetheless, previous studies investigating the roles of lncRNAs in AML only begin recently, and are quite limited, even though lncRNAs have been found to be crucial genetic factors in other malignancies. 18,19 In terms of the studies including RNA sequencing in AML, in a study using miRNA sequencing and transcription factor (TF) activity array, 308 dysregulated miRNAs and 84 dysregulated TFs are detected, then 1462 miRNA-target gene pairs, 982 TF-target gene pairs, and 196 TF-miRNA pairs are identified subsequently; after emerging as a regulatory network of these dysregulated miRNAs and TF, the KEGG pathway analysis finds that the network is markedly enriched in 33 pathways with the AML-related pathways the most significant. 20 Another previous study performs whole-genome microarrays in extramedullary infiltration (EMI) AML patients and non-EMI AML patients, and discloses that 253 circular RNAs (circRNAs) and 663 mRNAs are upregulated, but 259 circRNAs and 838 mRNAs are downregulated in EMI AML patients compared to non-EMI AML patients, then further enrichment analysis finds that these dysregulated circRNAs and mRNAs are mainly enriched in cell adhesion, migration, signal transduction, and cell to cell communications.…”
Section: Discussionmentioning
confidence: 99%